2018
DOI: 10.1111/bju.14554
|View full text |Cite
|
Sign up to set email alerts
|

Pathological upgrading at radical prostatectomy for patients with Grade Group 1 prostate cancer: implications of confirmatory testing for patients considering active surveillance

Abstract: Objective To examine the association between National Comprehensive Cancer Network (NCCN) risk, number of positive biopsy cores, age, and early confirmatory test results on pathological upgrading at radical prostatectomy (RP), in order to better understand whether early confirmatory testing and better risk stratification are necessary for all men with Grade Group (GG) 1 cancers who are considering active surveillance (AS). Patients and Methods We identified men in Michigan initially diagnosed with GG1 prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…Kaye et al investigated the postprostatectomy results of 1966 patients whose prostate biopsy result was Gleason grade group 1. In that study, the GU rates were 40% and 59% in patients with very low and low‐risk PCa, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaye et al investigated the postprostatectomy results of 1966 patients whose prostate biopsy result was Gleason grade group 1. In that study, the GU rates were 40% and 59% in patients with very low and low‐risk PCa, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported the association between the increased number of positive bioptic cores and GU in RP specimens. The authors emphasized that the GU in patients over the age of 70 was two‐fold higher than the GU in patients below 70 years old . In another study, Capitanio et al specified that the increased number of samples taken during prostate biopsy resulted in the statistical reduction in the GU rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk stratifications prior to treatment decisions are primarily based on biopsy Gleason Grade Group (GGG), clinical stage, and prostate-specific antigen (PSA) levels. Significant sampling error and morbidity associated with prostate biopsy complicates differentiation between aggressive and indolent disease so that post-radical prostatectomy (RP) upgrading and upstaging is common [5][6][7]. Recently, multi-parametric magnetic resonance imaging (mpMRI) showed improvements in risk stratification of men on AS and was recommended for enhancing enrolment and monitoring decision [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Reese et al evaluated 130 patients initially on AS who underwent RP and concluded that disease reclassification during AS was the only significant factor associated with adverse pathology (AP) at RP [10]. Other studies have looked at predictors of AP in patient populations eligible, but not enrolled in AS [11][12][13]. Only the PRIAS study included a statistical analysis of which variables observed during AS could predict AP at RP [9].…”
Section: Introductionmentioning
confidence: 99%